2004
DOI: 10.1165/rcmb.2003-0211oc
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-Mediated Mucin Secretion from Differentiated Human Bronchial Epithelial Cells

Abstract: Most current cell-based models for examining the regulation of mucin secretion demonstrate low signal-to-noise ratios, making experimental manipulation and data interpretation difficult. Using adenosine triphosphate (ATP) as a mucin secretagogue, we have developed a model of agonist-induced mucin secretion in differentiated human bronchial epithelial cells. Mucin secretory signals were estimated using enzyme-linked lectin assay, and typical signals of 300-400% of baseline were observed in response to a 30-min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 34 publications
4
84
1
Order By: Relevance
“…Kemp et al [27] found it to be inactive at a concentration of 10 μM on a number of different receptors. These included the following human GPCRs: the serotonin receptors 5-HT 1A , 5-HT 2A , 5-HT 2B , 5-HT 2C , 5-HT 6 , and 5-HT 7 , the adrenergic receptors α 1 , α 2A , α 2B , α 2C , β 1 , and β 2 , the cannabinoid receptor CB 1 , the dopamine receptors D 1 , D 2 Lh, D 3 , and D 4 , the muscarinic acetylcholine receptors M 1 , M 2 , M 3 , M 4 , and M 5 , the histamine receptors H 1 and H 2 , the tachykinin receptors NK 1 and NK 2 , the opioid receptors δ, κ, and μ, GABA B , as well as the rat P2Y 1 receptor.…”
Section: Pharmacological Evaluation Of Ar-c118925 (3) and Its Derivatmentioning
confidence: 99%
See 3 more Smart Citations
“…Kemp et al [27] found it to be inactive at a concentration of 10 μM on a number of different receptors. These included the following human GPCRs: the serotonin receptors 5-HT 1A , 5-HT 2A , 5-HT 2B , 5-HT 2C , 5-HT 6 , and 5-HT 7 , the adrenergic receptors α 1 , α 2A , α 2B , α 2C , β 1 , and β 2 , the cannabinoid receptor CB 1 , the dopamine receptors D 1 , D 2 Lh, D 3 , and D 4 , the muscarinic acetylcholine receptors M 1 , M 2 , M 3 , M 4 , and M 5 , the histamine receptors H 1 and H 2 , the tachykinin receptors NK 1 and NK 2 , the opioid receptors δ, κ, and μ, GABA B , as well as the rat P2Y 1 receptor.…”
Section: Pharmacological Evaluation Of Ar-c118925 (3) and Its Derivatmentioning
confidence: 99%
“…The panel further included the following human ion channels: 5-HT 3 , L-type and N-type calcium and ATP-sensitive potassium channels. They further assessed the human P2Y 2 receptor for antagonism in a sandwich enzyme-linked lectin assay measuring mucin secretion, where they determined an IC 50 value of approximately 1 μM upon receptor stimulation with 100 μM ATPγS [27].…”
Section: Pharmacological Evaluation Of Ar-c118925 (3) and Its Derivatmentioning
confidence: 99%
See 2 more Smart Citations
“…These G␣ subunits share over 80% homology in their amino acid sequences (45), hence their ability to inhibit the channel might reflect a promiscuous capacity to activate the same downstream signaling pathways, one of which inhibits ENaC. Gq/11-coupled GPCRs are known to regulate several cellular events in epithelial cells, including intracellular Ca 2ϩ mobilization (46), mucin secretion (47,48), and anion secretion (49). Our data suggest that, Gq/11 plays a small, but significant, part in the P2Y 2 receptor-mediated signaling mechanism that inhibits activity of ENaC.…”
Section: Discussionmentioning
confidence: 99%